Identification of Salmonella sp. Bacterial Contamination on Pempek Products Circulating in Urban Village of Ciracas, RW 08, East Jakarta - Lila Muliva Az Zahra; Dian Rachma Wijayanti; Suparlan Hadi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Pempek is a traditional Palembang food widely popular among the public, but it is vulnerable to contamination by pathogenic bacteria due to the use of raw ingredients and unhygienic processing. One of the bacteria commonly associated with fish-based food contamination is Salmonella sp., which can cause foodborne diseases. However, studies specifically examining Salmonella contamination in pempek, particularly at the local level in the Ciracas area, are still limited. This study aimed to determine the presence of Salmonella sp. contamination in pempek sold in Ciracas RW 08, East Jakarta. This study employed a descriptive observational design with a laboratory-based microbiological approach to detect Salmonella sp. contamination in pempek samples. The tested samples consisted of two fried samples and two boiled samples. Identification of Salmonella was carried out according to SNI 01-2332.2-2006, which includes three stages: pre-enrichment in Lactose Broth (LB), selective enrichment using Rappaport Vassiliadis (RV), and identification on Xylose Lysine Deoxycholate (XLD) medium. The results showed that one out of four pempek samples tested positive for Salmonella sp. A positive result was from boiled pempek. Overall, 25% pempek samples sold in Ciracas, RW 08 were contaminated with Salmonella sp. We recommend the Salmonella test for both raw and cooked home industry pempek.